Studi Kualitas Kandungan Logam Besi Dan Mangan Pada Air Sumur Bor Di Desa Polewali - Nur Susi Susanti B.; Abd. Gafur; Sumiaty (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Groundwater is widely used in Indonesia because it is readily available and generally considered of better quality. Groundwater is used for various purposes, such as household, agricultural, and industrial needs. This study aims to determine the quality of drilled well water based on the iron (Fe) and manganese (Mn) metal content consumed by residents of Polewali Village, South Baebunta District, North Luwu Regency. This is an observational study with a descriptive approach. The study population consisted of six drilled wells that served as water sources for the community. The results showed that of the six drilled wells examined, three contained no Fe, while the other three contained Fe at varying concentrations. Meanwhile, Mn was detected in all well water samples from the drilled wells. These findings indicate that the quality of drilled well water in Polewali Village varies between locations, with Fe content undetectable in some locations but relatively high in others, and Mn content found in all samples. Therefore, regular water quality monitoring and well water treatment are necessary, especially in locations where metal levels exceed quality standards, to ensure community water safety.